Analisis Pendapatan Usahatani Tomat Apel Di Desa Tonsewer Selatan Kecamatan Tompaso Barat Kabupaten Minahasa - Pelealu, Indri Veronika; Baroleh, Jenny; Jocom, Sherly G. (AGRI-SOSIOEKONOMI, 2023)
This study aims to determine the Apple Tomato Farming Income in South Tosewer Village, West Tompaso District, Minahasa Regency. This research was conducted from February to April 2023. The data collected included primary data obtained from direct interviews with tomato farmers as owners using questionnaires. Secondary data were obtained through research reports on the internet, journals and others related to the research. Sampling using purposive sampling method. The sample in the study amounted to 4 people who had tomato farms as owners and who harvested together in the last growing season. The research was analyzed using farm analysis, namely cost analysis, revenue, income and continued with the revenue cost ratio. The results showed that the average income obtained in Apple Tomato farming in South Tonsewer Village, West Tompaso District, Minahasa Regency was Rp52,098,950 per one planting period, which was obtained from the average revenue of Rp62,125,000 and the average total cost of Rp10,026,250. The R/C Ratio analysis shows that Apple Tomato farming in South Tonsewer Village, West Tompaso District, Minahasa Regency is feasible. This can be seen from the ratio of total income to total costs which is greater than one, namely 6.196.